Analisis Efektivitas Waktu Evakuasi pada Shelter Terminal 3 Skytrain (Kereta Layang) Bandara Internasional Soekarno-Hatta - Handoko; Sasqiya Putri, Destiana; Setyo Oktaria, Dhina (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
The purpose of this study was to analyze the passenger evacuation in the 3 skytrain terminal shelter and to determine the passenger capacity at the terminal shelter. Among the four terminals at this airport there are terminals that have a level of passenger mobility which is categorized quite dense. So that the implementation will appear various kinds of obstacles that may occur. One of them is an accident during operation. So the need for an evacuation process in accordance with the evacuation rules. It also resulted in the need for guidelines in conducting the evacuation process such as how long it would take for the evacuation process. This research method uses quantitative descriptive approach. The results of the study concluded that the effectiveness of the evacuation time required from the platform area to the concourse had met the standard. It's just that the effectiveness of the evacuation from the platform to the safe area has not met because it exceeds the standard with a time of 7.36 minutes real time in the field.